Curvaturas de métricas invariantes em Grupos de Lie - Sene, Renato Tolentino de (2015)
In this work we study the geometric aspects of Lie groups from the view point of the Riemannian geometry, by means of invariant geometric structures associated. We present some properties on curvatures of metrics left invariants and bi-invariant one on Lie groups. We also present a treatment of the Lie algebras unimodular, including the tridimensional case. Most of the results studied are from the article of John Milnor: Curvatures of Left Invariant Metrics on Lie Groups.